Anacroneuria (Plecoptera: Perlidae) from Central Brazil: new species, new geographic records, and taxonomic notes - Miguel, Marina; de Almeida, Lucas Henrique; Novaes, Marcos Carneiro; Da Conceição Bispo, Pitágoras (Zootaxa, 2022)
In the present study, adult specimens of Anacroneuria collected in streams were studied in order to understand the diversity of the genus in Central Brazil. Herein, a new species (A. froehlichi n. sp.) is described, new geographic occurrences are recorded (A. amargosa Righi-Cavallaro & Froehlich, 2013; A. mineira Novaes & Bispo, 2014; A. minuta Klapálek, 1922; A. ofaye Froehlich, 2007; A. payagua Froehlich, 2007; A. singela Duarte & Lecci, 2016; and A. singularis Righi-Cavallaro & Lecci, 2010), and taxonomic comments are made. Additionally, photographs of the paratypes of A. dourada Jewett, 1960 and A. galba Jewett, 1960 are presented. A total of 16 species of Anacroneuria are now recorded in Central Brazil.